Faster and safer? FLASH ultra-high dose rate in radiotherapy - Durante, Marco (Br J Radiol, 2018)
Recent results from the Franco-Swiss team of Institute Curie and Centre Hospitalier Universitaire Vaudois demonstrate a remarkable sparing of normal tissue after irradiation at ultra-high dose rate (>40 Gy s(−1)). The “FLASH” radiotherapy maintains tumour control level, suggesting that ultra-high dose rate can substantially enhance the therapeutic window in radiotherapy. The results have been obtained so far only with 4–6 MeV electrons in lung and brain mouse model. Nevertheless, they have attracted a great attention for the potential clinical applications. Oxygen depletion had been discussed many years ago as a possible mechanism for reduction of the damage after exposure to ultra-high dose rate. However, the mechanism underlying the effect observed in the FLASH radiotherapy remains to be elucidated.